Adhesive resin composition, adhesive resin layer, metal substrate with adhesive, and laminate
By using a specific proportion of the adhesive resin composition of polyimide resin, maleimide compound, free radical initiator and epoxy resin, the problem of reducing bond strength caused by the low surface roughness of the metal layer during high frequency transmission is solved, and the balance of low dielectric properties and high bond strength is achieved.
Patent Information
- Application Number
- CN202411324250.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-09-23
- Publication Date
- 2025-04-01
AI Technical Summary
In high-frequency transmission, the low surface roughness of the metal layer leads to a reduction in the anchoring effect of the adhesive, and the adhesion of the laminated material also decreases, making it difficult to achieve both low dielectric properties and high bonding strength.
An adhesive resin composition including a polyimide resin, a maleimide compound, a radical initiator, and an epoxy resin is used to form an adhesive resin layer with low dielectric properties by adjusting the proportion of these components and the content of additives, and sufficient adhesive strength is achieved on the metal layer.
An adhesive resin composition with low dielectric properties in the high frequency region is realized, and the adhesion strength is sufficient, and it is suitable for circuit substrates with high speed transmission.
Smart Images

Figure CN119736021A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive resin composition, an adhesive resin layer, a metal substrate with an adhesive, and a laminate. Background Art
[0002] Circuit boards for high-speed transmission are required to have low dielectric properties (low dielectric constant, low dielectric loss tangent) in a high-frequency region (see, for example, Patent Documents 1 to 7).
[0003] Patent Document 1: Japanese Patent Application Publication No. 2023-39241
[0004] Patent Document 2: Japanese Patent Application Publication No. 2023-68801
[0005] Patent Document 3: Japanese Patent Application Publication No. 2023-75383
[0006] Patent Document 4: Japanese Patent Application Publication No. 2023-76131
[0007] Patent Document 5: Japanese Patent Application Publication No. 2023-87152
[0008] Patent Document 6: International Publication No. 2022 / 004583
[0009] Patent Document 7: Japanese Patent No. 7287380 Summary of the invention
[0010] In high frequency transmission, in order to reduce the transmission loss caused by the skin effect, there is a tendency to use a metal layer with a small surface roughness. When the surface roughness of the metal layer is small, it is difficult to obtain an anchor effect on the adhesive, and the adhesion with the laminated material is reduced.
[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an adhesive resin composition having low dielectric properties in a high frequency region and capable of ensuring sufficient bonding strength, and an adhesive resin layer, an adhesive-attached metal substrate, and a laminate using the adhesive resin composition.
[0012] The present invention includes the following aspects.
[0013] The adhesive resin composition involved in the first embodiment is an adhesive resin composition comprising a polyimide resin (A), a maleimide compound (B), a free radical initiator and an epoxy resin (C), wherein the weight ratio of the polyimide resin (A) to the maleimide compound (B) is 10:1 to 3:2, the content of the free radical initiator is 1 part by weight or more and less than 15 parts by weight relative to 100 parts by weight of the maleimide compound (B), and the content of the free radical initiator is 1 part by weight or more and less than 15 parts by weight relative to 100 parts by weight of the polyimide compound (B). The total amount of the imide resin (A) and the maleimide compound (B) is 100 parts by weight, the content of the epoxy resin (C) is 0.5 parts by weight or more and 5 parts by weight or less, and when the adhesive resin composition is measured under the following conditions (1) and (2), the dielectric loss tangent (Df value) when humidified is 0.0030 or less, and the difference between the dielectric loss tangent (Df value) when dry and the dielectric loss tangent (Df value) when humidified is 0.0003 or less.
[0014] (1) The dielectric loss tangent (Df value) when dried was measured after the coating was dried and then heated to completely cure the coating and to set the solvent content to 1 wt % or less, and then left at 135° C. for 1 hour.
[0015] (2) The dielectric loss tangent (Df value) during humidity control was measured after the coating was dried and then heated to completely cure the coating and to set the solvent content to 1 wt % or less, and then left to stand at 23° C. and 50% relative humidity for 24 hours.
[0016] The adhesive resin layer according to the second aspect is formed from the adhesive resin composition according to the first aspect.
[0017] The metal substrate with an adhesive according to the third aspect has a metal layer on one or both surfaces of the adhesive resin layer formed from the adhesive resin composition according to the first aspect.
[0018] The laminated body according to the fourth aspect has the metal substrate with an adhesive according to the third aspect on one or both surfaces of the laminated material.
[0019] According to the present invention, there can be provided an adhesive resin composition having low dielectric properties in a high frequency region and capable of ensuring sufficient adhesive strength, and an adhesive resin layer, an adhesive-attached metal substrate, and a laminate using the adhesive resin composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a cross-sectional view showing a first example of a metal substrate with an adhesive.
[0021] Figure 2 It is a cross-sectional view showing a second example of the metal substrate with an adhesive.
[0022] Figure 3 It is a cross-sectional view showing a first example of the laminated body.
[0023] Figure 4 It is a cross-sectional view showing a second example of the laminated body.
[0024] (Explanation of Reference Numerals)
[0025] 10 ...metal layer, 11 ...adhesive resin layer, 12 ...laminated material, 21, 22 ...metal substrate with adhesive, 23, 24 ...laminated body. DETAILED DESCRIPTION
[0026] Hereinafter, the present invention will be described based on preferred embodiments.
[0027] The adhesive resin composition according to the present embodiment includes a polyimide resin (A), a maleimide compound (B), a radical initiator, and an epoxy resin (C).
[0028] [Polyimide resin (A)]
[0029] The polyimide resin (A) is not particularly limited and may be a reactant of a diamino compound and a tetrabasic acid dianhydride. In addition, the polyimide resin (A) may be chemically modified at least one end, side chain, etc. The adhesive resin composition may contain at least one polyimide resin (A) or may contain two or more.
[0030] The diamino compound used for synthesis of the polyimide resin (A) is not particularly limited, and examples thereof include aliphatic diamino compounds and aromatic diamino compounds.
[0031] Examples of the aliphatic diamino compound include one or two or more of hexamethylenediamine, 1,3-bis(aminomethyl)cyclohexane, and the like.
[0032] Examples of the aromatic diamino compound include one or more of 9,9-bis(4-aminophenyl)fluorene, 4,4-oxydiphenylamine, 1,3-bis(3-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane [also known as 4,4'-(hexafluoroisopropylidene)bis(2-aminophenol)].
[0033] The tetrabasic acid dianhydride used for the synthesis of the polyimide resin (A) is not particularly limited, and examples thereof include one or more of 4,4′-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic anhydride, 3,3′,4,4′-benzophenonetetracarboxylic dianhydride, hydroxydiphthalic anhydride, and pyromellitic dianhydride.
[0034] [Maleimide compound (B)]
[0035] The maleimide compound (B) is not particularly limited as long as it is a compound having one or more maleimide groups in one molecule, and preferably a compound having two or more maleimide groups in one molecule. The maleimide compound (B) can be obtained by reacting an amino compound having one or more amino groups in one molecule with maleic anhydride. The adhesive resin composition may contain at least one maleimide compound (B) or two or more.
[0036] Examples of the amino compound used for the synthesis of the maleimide compound (B) include 3,4,4′-triaminodiphenylmethane, triaminophenol, tris(4-aminophenyl)phosphate, tris(4-aminophenyl)phosphate, tris(4-aminophenyl)thiophosphate, and triethylenetetramine.
[0037] Specific examples of the maleimide compound (B) include: trimaleimide compounds such as tris(4-maleimidophenyl)methane; tetramaleimide compounds such as bis(3,4-dimaleimidophenyl)methane, tetramaleimidobenzophenone, and tetramaleimidonaphthalene; phenol linear novolac type maleimide resins, isopropylidene bis(phenoxyphenylmaleimide)phenylmaleimide aralkyl resins, biphenylene type phenylmaleimide aralkyl resins, etc.
[0038] [Free Radical Initiator]
[0039] The maleimide compound (B) can self-crosslink the maleimide groups under the action of a free radical initiator. Self-crosslinking can improve the heat resistance of the solder. Examples of free radical initiators include organic peroxides such as dicumyl peroxide and dibutyl peroxide; azo compounds such as 2,2'-azobis(isobutyronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile). The adhesive resin composition only needs to contain at least one free radical initiator, and may contain two or more.
[0040] The content of the free radical initiator is 1 part by weight or more and less than 15 parts by weight, preferably 3 parts by weight or more and 10 parts by weight or less, relative to 100 parts by weight of the maleimide compound (B). If the content of the free radical initiator is within the above range, the adhesive resin composition having low dielectric properties in the high frequency region is easy to fully ensure the bonding strength for the metal layer used in the high frequency region.
[0041] [Epoxy resin (C)]
[0042] The epoxy resin (C) is a bifunctional or higher epoxy resin having two or more epoxy groups in one molecule. Specific examples include bisphenol A epoxy resin, bisphenol F epoxy resin, phenol novolac epoxy resin, glycidylamine epoxy resin, naphthalene epoxy resin, glycidyl ether epoxy resin, and phenoxy resins that are reactants of bisphenol epoxy resins and epichlorohydrin. The adhesive resin composition may contain at least one epoxy resin (C) and may contain two or more.
[0043] The epoxy resin (C) is preferably a low molecular weight compound having a molecular weight of less than 370. The molecular weight of the epoxy resin (C) may be, for example, 200 or more.
[0044] The epoxy equivalent of the epoxy resin (C) is preferably 160 or less, and more preferably 150 or less. The epoxy equivalent of the epoxy resin (C) may be, for example, 90 or more.
[0045] For more than two epoxy groups contained in epoxy resin (C), the shortest number of atoms contained between the epoxy groups is preferably less than 9 atoms, more preferably less than 3 atoms. It should be noted that the above-mentioned "epoxy group" refers to a cyclic ether structure (ethylene oxide ring) of a 3-membered ring, and the above-mentioned "shortest number of atoms" refers to: the number of atoms on the path that does not include the atoms contained in each ethylene oxide ring and connects any two ethylene oxide rings via the shortest covalent bond. As the covalent bond, CC, CN, CO, etc. can be listed, preferably peroxide bonds (OO) and the like are not included. In addition, in the case of a cyclic structure included in the path, the shortest path inside the cyclic structure is selected. In the case where multiple ethylene oxide rings are directly linked by covalent bonds between carbon C in the ring, the shortest number of atoms is recorded as 0 atoms. The shortest number of atoms is preferably more than 1 atom, more preferably more than 3 atoms.
[0046] When the epoxy resin (C) contains an epoxy compound having a cyclic structure, it is preferably an epoxy resin having one cyclic structure or an epoxy resin having a structure formed by connecting two cyclic structures. As the cyclic structure, heterocyclic structures of more than 4 rings or cyclic hydrocarbon structures can be listed. As the heterocyclic structure, pyridine ring, thiophene ring, etc. can be listed. As the cyclic hydrocarbon structure, alicyclic hydrocarbon structures such as cyclohexane ring, or aromatic hydrocarbon structures such as benzene ring and naphthalene ring can be listed.
[0047] [Adhesive resin composition]
[0048] In the adhesive resin composition of the present embodiment, the weight ratio of the polyimide resin (A) to the maleimide compound (B) is 10: 1 to 3: 2, preferably 7: 1 to 5: 2. If the weight ratio of these compounds is within the above range, the adhesive resin composition having low dielectric properties in the high frequency region is easy to fully ensure the bonding strength for the metal layer used in the high frequency region.
[0049] In the adhesive resin composition according to the present embodiment, the content of the epoxy resin (C) is 0.5 parts by weight or more and 5 parts by weight or less based on 100 parts by weight of the total of the polyimide resin (A) and the maleimide compound (B).
[0050] If the content of the epoxy resin (C) is above the above lower limit, the epoxy group remaining without reacting with the polyimide group of the polyimide resin (A) can form a chemical bond (e.g., a hydrogen bond) with the surface of the metal layer, so it is easy to fully ensure the bonding strength for the metal layer used in the high-frequency region. If the content of the epoxy resin (C) is below the above upper limit, it is easy to fully ensure the bonding strength while maintaining the low dielectric properties of the adhesive resin composition in the high-frequency region.
[0051] The adhesive resin composition may contain an organic solvent. Examples of the organic solvent include one or more selected from ester solvents, amide solvents, sulfone solvents, ether solvents, ketone solvents, aromatic solvents, and the like.
[0052] Specific examples of the ester solvent include γ-butyrolactone and the like.
[0053] Specific examples of the amide solvent include N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and N,N-dimethylimidazolidinone.
[0054] Specific examples of the sulfone-based solvent include tetramethylene sulfone and the like.
[0055] Specific examples of the ether solvent include diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether monoacetate, and propylene glycol monobutyl ether.
[0056] Specific examples of the ketone solvent include methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone.
[0057] Specific examples of the aromatic solvent include toluene, xylene, and anisole.
[0058] The organic solvent is preferably used in a ratio such that the solid content concentration in the adhesive resin composition excluding the organic solvent is 10 wt % to 80 wt %, more preferably 20 wt % to 70 wt %.
[0059] The adhesive resin composition can be prepared by adding a main agent including a polyimide resin (A) and a maleimide compound (B) to an organic solvent, and further adding a radical initiator and an epoxy resin (C).
[0060] When the adhesive resin composition according to the present embodiment is measured under the following conditions (1) and (2), the dielectric loss tangent (Df value) in humidity control is 0.0030 or less, and the difference between the dielectric loss tangent (Df value) in dry state and the dielectric loss tangent (Df value) in humidity control is 0.0003 or less.
[0061] (1) The first condition is that the dielectric loss tangent (Df value) when dry is measured after coating and drying, after further heating to completely cure the coating, and after the solvent content is set to 1 wt % or less, and after the coating is left at 135° C. for 1 hour.
[0062] (2) The dielectric loss tangent (Df value) during humidity control was measured after the coating was dried and then heated to completely cure the coating and the solvent content was set to 1 wt % or less and then left to stand at 23° C. and 50% relative humidity for 24 hours.
[0063] The state of complete curing is recorded as complete curing when the degree of curing obtained by (calorific value before curing - calorific value after curing) / calorific value before curing × 100 (%) is 90% or more in DSC measurement (temperature increase rate 10°C / min). The calorific value before curing is the total calorific value of the sample before curing. The calorific value after curing is the residual calorific value of the sample after curing.
[0064] The solvent content can be determined, for example, as the weight loss when the temperature is increased from 30°C to 250°C in TG-DTA measurement (temperature increase rate 10°C / min). The dielectric loss tangent (Df value) when dried can be measured after leaving the sample at 135°C for 1 hour in a state where the solvent content is 1 wt% or less.
[0065] The dielectric loss tangent (Df value) during humidity control is preferably 0.0023 or less, more preferably 0.0020 or less, and even more preferably less than 0.0020.
[0066] Inorganic fillers and the like may be added to the adhesive resin composition as known additives. Examples of the inorganic filler include, but are not particularly limited to, silica, alumina, calcium carbonate, titanium oxide, glass fiber, and glass powder.
[0067] [Adhesive resin layer]
[0068] The adhesive resin layer of the present embodiment is formed by the above-mentioned adhesive resin composition. The adhesive resin layer can be any stage of uncured, semi-cured, and fully cured. The adhesive resin layer of the present embodiment can be a single-layer adhesive resin layer, or a multi-layer adhesive resin layer, or a monomer in a state not stacked on other layers, or a composite laminate in a state stacked on other layers.
[0069] The thickness of the adhesive resin layer is not particularly limited, and is preferably 1 μm or more and 100 μm or less. As a specific example of the thickness of the adhesive resin layer, it is not particularly limited, and can be cited as a numerical range with any two of the numerical group consisting of 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm and 100 μm as the upper limit and lower limit.
[0070] The adhesive resin layer may contain a material derived from the adhesive resin composition, or may be composited with a material other than the adhesive resin composition. For example, the adhesive resin layer may contain an inorganic filler and / or glass cloth.
[0071] [Metal substrate with adhesive]
[0072] The metal substrate with an adhesive according to the present embodiment has a metal layer on one or both surfaces of an adhesive resin layer formed from the above-mentioned adhesive resin composition.
[0073] Figure 1 The metal substrate 21 with adhesive shown has a metal layer 10 on one side of an adhesive resin layer 11 . Figure 2 The metal substrate 22 with adhesive shown has metal layers 10 on both sides of an adhesive resin layer 11 , and is laminated in the order of metal layer 10 / adhesive resin layer 11 / metal layer 10 .
[0074] The metal substrates 21 and 22 with adhesive are combined with any low-dielectric substrate and thermally laminated to produce circuit substrates such as flexible substrates (FPC) and rigid substrates (PCB) for high-speed transmission.
[0075] Any conductive material that can be used for a circuit board can be used for the metal layer 10. Specific examples of the conductive material include metals such as copper (Cu), aluminum (Al), iron (Fe), zinc (Zn), and nickel (Ni); and alloys containing at least one of these metal elements. Examples of the alloy include stainless steel (SUS), steel, and copper alloys.
[0076] Among them, as the metal layer 10, metal foil is preferred, and copper foil is more preferred. Among the copper foils, rolled copper foil and electrolytic copper foil can be used. The raw material of the copper foil can be pure copper or a copper alloy. As the copper alloy, alloys in which trace amounts of tin (Sn), silver (Ag) and other components are added to copper (Cu) can be cited.
[0077] The metal layer 10 is preferably a metal foil having a surface roughness of 1.5 μm or less. In the case of copper foil, it can be a low-profile copper foil or a non-profile copper foil. Low-profile copper foil is a copper foil having a surface roughness of 1.5 μm or less, preferably 1.4 μm or less, and particularly preferably 1.3 μm or less. Non-profile copper foil is a copper foil having a surface roughness of 0.85 μm or less, more preferably 0.84 μm or less, and particularly preferably 0.82 μm or less. The surface roughness in this specification refers to the ten-point average roughness (RzJIS).
[0078] In the present embodiment, even when a flat copper foil is used as the metal layer 10 , a metal base material with an adhesive and a laminated body capable of sufficiently ensuring the bonding strength between the laminate material and the metal layer can be obtained.
[0079] The thickness of the metal layer 10 is not particularly limited, and may be any combination of a lower limit selected from 1.5 μm or more, 3 μm or more, and 10 μm or more, and an upper limit selected from 175 μm or less, 100 μm or less, and 70 μm or less.
[0080] [Laminated body]
[0081] The laminated body of the present embodiment has the above-mentioned metal substrate with an adhesive on one side or both sides of the laminated material. Figure 3 The laminated body 23 shown has a metal substrate 21 with an adhesive on one side of the laminated material 12 . Figure 4 The laminated body 24 shown has metal substrates 21 with adhesive on both sides of the laminated material 12 .
[0082] The metal substrate 21 with adhesive contained in the stack 23, 24 is bonded to the stack material 12 with the surface opposite to the surface where the adhesive resin layer 11 contacts the metal layer 10, and is stacked in the order of metal layer 10 / adhesive resin layer 11 / stacking material 12, or metal layer 10 / adhesive resin layer 11 / stacking material 12 / adhesive resin layer 11 / metal layer 10.
[0083] The laminating material is not particularly limited as long as it is a material used as a laminate, and examples thereof include films, sheets, boards, and the like formed from resins such as modified polyimide resins, polyester resins, liquid crystal polymers, cyclic olefin resins, polyphenylene ether resins, polyphenylene sulfide resins, polyetheretherketone resins, bismaleimide resins, triazine resins, benzocyclobutene resins, and low dielectric epoxy resins.
[0084] The laminated material may be a prepreg. The prepreg may contain an inorganic filler, may contain both glass cloth and an inorganic filler, or may be a structure in which the glass cloth is impregnated with a resin.
[0085] When a polyimide resin film or a modified polyimide resin film is used as the low-dielectric base material, an FPC is obtained.
[0086] If a prepreg using, for example, a polyphenylene ether resin is used as the low-dielectric base material, a rigid substrate can be produced.
[0087] In the laminated bodies 23 and 24 , the thickness of the adhesive resin layer 11 is preferably 0.5 μm or more and 100 μm or less, and more preferably 1 μm or more and 50 μm or less.
[0088] The thickness of the laminated material 12 is preferably 3 μm or more and 3200 μm or less, and more preferably 10 μm or more and 200 μm or less.
[0089] The thickness of the metal layer 10 is preferably 1.5 μm or more and 175 μm or less, and more preferably 3 μm or more and 70 μm or less.
[0090] When the metal layer 10 includes a copper layer such as copper foil, the laminates 23 and 24 may be copper clad laminates (CCL).
[0091] As mentioned above, although this invention was demonstrated based on the suitable embodiment, this invention is not limited to the said embodiment, Various changes are possible within the range which does not deviate from the summary of this invention.
[0092] Example
[0093] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited to these examples.
[0094] [Preparation of Adhesive Resin Composition]
[0095] The polyimide resin (A), the maleimide compound (B), the epoxy resin (C), the curing accelerator and the free radical initiator were mixed in the proportions shown in the solid content of Tables 1 to 6. In any example, the proportions of 80 parts by weight of the polyimide resin (A), 20 parts by weight of the maleimide compound (B) and 1.2 parts by weight of the free radical initiator were used, and the proportions of the epoxy resin (C) and the curing accelerator were changed as shown in Tables 1 to 6. The adhesive resin composition having a solid content concentration of 40% by weight or 23% by weight was prepared by diluting with toluene.
[0096] [Epoxy resin (C)]
[0097] In Examples 1-1 and 1-2 shown in Table 1, a tetrafunctional alicyclic glycidylamine epoxy resin (manufactured by Mitsubishi Gas Chemical Corporation, TETRAD (registered trademark)-C, component: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane) was used.
[0098] In Examples 2-1 and 2-3 shown in Table 2, a tetrafunctional aromatic glycidylamine-type epoxy resin (manufactured by Mitsubishi Gas Chemical Co., Ltd., TETRAD (registered trademark)-X, component: N,N,N',N'-tetraglycidyl-meta-xylylenediamine) was used.
[0099] In Examples 3-1 and 3-4 shown in Table 3, a bifunctional naphthalene-type epoxy resin (manufactured by DIC Corporation, EPICLON (registered trademark) HP-4032D, component: 1,6-bis(glycidoxy)naphthalene) was used.
[0100] In Examples 4-1 to 4-3 shown in Table 4, a trifunctional epoxy resin (jER (registered trademark) 630 manufactured by Mitsubishi Chemical Corporation, component: N,N-diglycidyl-4-(glycidoxy)aniline) was used.
[0101] In Examples 5-1 and 5-2 shown in Table 5, a difunctional aromatic glycidylamine-type epoxy resin (GAN manufactured by Nippon Kayaku Co., Ltd., component: N,N-diglycidylaniline) was used.
[0102] In Comparative Example 1 shown in Table 6, the epoxy resin (C) and the curing accelerator were not used.
[0103] In Comparative Examples 2-1 and 2-2 shown in Table 6, a bifunctional bisphenol A epoxy resin (jER (registered trademark) 828EL manufactured by Mitsubishi Chemical Corporation) was used.
[0104] In Comparative Examples 3-1 and 3-2 shown in Table 6, a trifunctional trisphenol methane epoxy resin (EPPN-502H manufactured by Nippon Kayaku Co., Ltd.) was used.
[0105] [Manufacturing of metal substrate with adhesive]
[0106] The adhesive resin composition having a solid content concentration of 40% by weight of each Example and each Comparative Example was applied to a 18 μm thick non-profile copper foil (manufactured by Fukuda Metal Foil Powder Co., Ltd., Japan, CF-T9DA-SV) using a coater so that the thickness of the adhesive resin layer after drying was about 40 μm, and then dried at 120° C. to produce a metal substrate 1 with an adhesive. Furthermore, a copper foil was laminated on the resin-coated surface of the metal substrate 1 with an adhesive, and lamination was performed at 200° C. for 60 minutes under the condition of 3 MPa to produce a metal substrate 2 with an adhesive (Cu / Ad / Cu).
[0107] [Manufacturing of Laminated Body]
[0108] On a profile-free copper foil with a thickness of 18 μm (manufactured by Fukuda Metal Foil Powder Co., Ltd., Japan, CF-T9DA-SV), a wire rod coater was used to apply the adhesive resin composition with a solid content concentration of 23% by weight of each embodiment and each comparative example so that the thickness of the adhesive resin layer after drying became 3 μm, and then it was dried at 120°C to manufacture two sets of metal substrates with adhesives in the same style. These metal substrates with adhesives were stacked in the order of copper foil / adhesive resin layer / prepreg / adhesive resin layer / copper foil, and laminated at 195°C for 100 minutes under the condition of 3.0 MPa to manufacture a laminate (double-sided CCL). The prepreg used was MEGTRON (registered trademark) 6 manufactured by Panasonic Industries, Ltd. of Japan.
[0109] [Measurement of dielectric loss tangent (Df value)]
[0110] The obtained metal substrate 1 with adhesive was cured at 200°C for 60 minutes under vacuum conditions. The copper foil was further removed by etching, and the dielectric loss tangent (Df value) in the dry state and the dielectric loss tangent (Df value) in the humidified state were measured at a frequency of 10 GHz using a dielectric constant measuring device (cavity resonator type, manufactured by ATE) according to the above conditions (1) and (2).
[0111] [Solder heat resistance test]
[0112] The metal substrate with adhesive and the laminate (double-sided CCL) of each embodiment and each comparative example were dried at 135°C for 1 hour, floated in a solder bath at 288°C, and the time until deformation or blistering occurred was measured to evaluate heat resistance. The case where no deformation or blistering occurred within 600 seconds was evaluated as acceptable.
[0113] [Peel Adhesion Strength of Metal Substrate 2 with Adhesive (Cu / Ad / Cu)]
[0114] The bonding strength between the copper foils was measured for the obtained metal substrate 2 with an adhesive (Cu / Ad / Cu).
[0115] The obtained metal substrate 2 with an adhesive (Cu / Ad / Cu) was cut into a piece with a width of 10 mm to obtain a test piece.
[0116] One copper foil portion was attached to a ring core having a diameter of 11 cm, and the other copper foil portion was pulled at a speed of 50 mm / min to perform a 90° peel test.
[0117] As an index of the bonding strength between copper foils, 0.85 N / mm or more was regarded as an acceptable value.
[0118] [Peel Adhesion Strength of Laminated Body (Double-Sided CCL)]
[0119] The bonding strength between the copper foil and the prepreg was measured for the obtained laminate (double-sided CCL). The obtained laminate (double-sided CCL) was cut into a 10 mm width to obtain a test piece.
[0120] The prepreg side was attached to a toroidal core having a diameter of 11 cm, and the copper foil portion was pulled at a speed of 50 mm / min to perform a 90° peel test.
[0121] As an index of the bonding strength between the copper foil and the prepreg, a value of 0.53 N / mm or more was regarded as an acceptable value.
[0122] The results are shown in Tables 1 to 6.
[0123]
Table 1
[0124]
[0125]
Table 2
[0126]
[0127]
[0128]
Table 3
[0129]
[0130]
Table 4
[0131]
[0132]
Table 5
[0133]
[0134]
[0135]
Table 6
[0136]
[0137] According to the adhesive resin composition of the example, an adhesive resin layer having a dielectric loss tangent (Df value) of 0.0030 or less when humidified and a difference between the dielectric loss tangent (Df value) when dry and the dielectric loss tangent (Df value) when humidified being 0.0003 or less is obtained.
Claims
1. An adhesive resin composition comprising a polyimide resin A, a maleimide compound B, a free radical initiator and an epoxy resin C, characterized in that: The weight ratio of the polyimide resin A to the maleimide compound B is 10:1 to 3:
2. The content of the free radical initiator is 1 part by weight or more and less than 15 parts by weight relative to 100 parts by weight of the maleimide compound B. The content of the epoxy resin C is 0.5 parts by weight or more and 5 parts by weight or less relative to 100 parts by weight of the total of the polyimide resin A and the maleimide compound B. When the adhesive resin composition is measured under the following conditions (1) and (2), the dielectric loss tangent Df value when humidified is 0.0030 or less, and the difference between the dielectric loss tangent Df value when dry and the dielectric loss tangent Df value when humidified is 0.0003 or less. Measurement conditions: (1) The dielectric loss tangent Df value when dry is measured after the coating is dried, the coating is further heated to a completely cured state and the solvent content is set to less than 1 wt %, and then the coating is left at 135°C for 1 hour. (2) The dielectric loss tangent Df value during humidity control was measured after the coating was dried and then heated to completely cure the coating so that the solvent content was 1 wt % or less and then left to stand at 23° C. and a relative humidity of 50% for 24 hours. 2 . An adhesive resin layer formed from the adhesive resin composition according to claim 1 . 3 . A metal substrate with an adhesive, comprising a metal layer on one or both sides of an adhesive resin layer formed from the adhesive resin composition according to claim 1 . 4 . A laminated body comprising the metal substrate with an adhesive according to claim 3 on one or both sides of a laminated material.
Citation Information
Patent Citations
Polyimide resin, resin composition containing the polyimide resin and cured product of the same
JP2023039241A
Polyimide resin composition and cured product of the same
JP2023068801A
Polyimide resin composition and cured body thereof
JP2023075383A
Polyimide resin, resin composition containing the polyimide resin and cured product of the same
JP2023076131A
Polyimide resin, resin composition comprising polyimide resin and cured product thereof
JP2023087152A